2018
DOI: 10.1080/15538362.2018.1493960
|View full text |Cite
|
Sign up to set email alerts
|

Water use and fruit yield of mango (Mangifera indicaL.) grown in a subtropical Mediterranean climate

Abstract: Mango (Mangifera indica L.) is one of the most important fruit crops in tropical and subtropical regions worldwide. On the coast of Granada and Malaga (SE Spain), irrigated subtropical fruit species have been introduced and cultivated on terraces with a considerable economic importance as the only European production region. The subtropical fruit production in this zone is possible with intensive irrigation on terraces, which are economically more profitable than traditional rainfed crops (almond and olive), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Localized irrigation methods were used in all studies. Two studies were developed in Petrolina, Brazil (Azevedo et al, 2003;Teixeira et al, 2008), two in Granada, Spain (Rodríguez Pleguezuelo et al, 2011;Durán-Zuazo et al, 2019a) and one in Israel (Levin et al, 2018). The highest K c mid value of the set of studies was reported by Teixeira et al (2008) in a low-density orchard with the tallest, more vigorous trees.…”
Section: Tropical and Subtropical Fruit Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…Localized irrigation methods were used in all studies. Two studies were developed in Petrolina, Brazil (Azevedo et al, 2003;Teixeira et al, 2008), two in Granada, Spain (Rodríguez Pleguezuelo et al, 2011;Durán-Zuazo et al, 2019a) and one in Israel (Levin et al, 2018). The highest K c mid value of the set of studies was reported by Teixeira et al (2008) in a low-density orchard with the tallest, more vigorous trees.…”
Section: Tropical and Subtropical Fruit Cropsmentioning
confidence: 99%
“…The studies performed for mango (Mangifera indica L.) used diverse methods to estimate crop ET. Teixeira et al (2008) used BREB;Azevedo et al (2003) and Levin et al (2018) used SWB while Rodríguez Pleguezuelo et al (2011) and Durán-Zuazo et al (2019a used drainage lysimeters. Localized irrigation methods were used in all studies.…”
Section: Tropical and Subtropical Fruit Cropsmentioning
confidence: 99%
“…Worldwide, mango is one of the most important nutritional and cash tree fruit crops in tropical and subtropical regions [9]. The crop provides income and sustains food and nutritional security for approximately 25% of the smallholder farmers in sub-Saharan Africa [8].…”
Section: Introductionmentioning
confidence: 99%
“…A system with a uniformity co-efficient of at least 85% is considered appropriate to meet standard design requirements [JAMREY, NIGAM 2018]. The fruit yield with full water demand met (100% potential crop evapotranspiration -ETc) averaged 24.1 kg•tree −1 , amounting to 21.2 kg•ha −1 •mm −1 in terms of water-use efficiency [DURÁN ZUAZO et al 2019]. In the drip irrigation method, water movement and its distribution in soil depend upon many parameters, e.g.…”
Section: Introductionmentioning
confidence: 99%